Retail payments and the real economy - Iftekhar Hasan; Tania De Renzis; Heiko Schmiedel (European Central Bank (ECB), 2013)
This paper examines the fundamental relationship between retail payments and the real economy. Using data from across 27 European markets over the period 1995-2009, the results confirm that migration to efficient electronic retail payments stimulates the overall economy, consumption and trade. Among different payment instruments, this relationship is strongest for card payments, followed by credit transfers. Cheque payments are found to have a relatively low macroeconomic impact. Retail payment transaction technology itself is also associated positively to real economic aggregates. We also show that initiatives to integrate and harmonise retail payment markets foster trade and consumption and thereby have a beneficial effect for whole economy. Additionally, the findings reveal that the impact of retail payments on the real economy is more pronounced in euro area countries. Our findings are robust to different regression specifications. The study supports the adoption of policies promoting a swift migration to efficient and harmonised electronic payment instruments.
Keywords: G20; G21; 330; Financial Development; Real economy; Retail payments